Production of Recombinant Human Aldehyde Oxidase in Escherichia coli and Optimization of Its Application for the Preparative Synthesis of Oxidized Drug Metabolites. Issue 4 (26th March 2014) - Rodrigues, Diogo; Kittelmann, Matthias; Eggimann, Fabian; Bachler, Thorsten; Abad, Sandra; Camattari, Andrea; Glieder, Anton; Winkler, Margit; Lütz, Stephan
Abstract: Recombinant human aldehyde oxidase (AO) was expressed in Escherichia coli . Different cell disruption methods and conditions of cell culture in shake flasks and bioreactors and of biotransformation on an analytical scale were tested to optimize the synthesis of oxidized AO drug metabolites. The volumetric productivity was increased 24‐fold by optimizing the cell culture conditions. The highest yield was achieved in a 25 L stirred tank bioreactor under non‐oxygen‐limited conditions and high lactose feed rate. Suspensions of highly concentrated and well‐aerated whole cells at neutral pH and relatively low temperatures led to the best conversion. The solvent for the substrate and the buffering agent for the biotransformation had an important effect. In a biotransformation with AO, 210 mg of famciclovir was converted to diacetyl penciclovir a yield of 82 %. The optimized protocol represents a viable method for the preparative synthesis of oxidized AO metabolites of drugs. Abstract : Drug metabolites: Recombinant human aldehyde oxidase is expressed in Escherichia coli. The highest volumetric productivity is achieved in a 25 L stirred tank bioreactor under non‐oxygen‐limited conditions and high lactose feed rate. In a biotransformation with concentrated whole cells at pH 7.4 and 30 °C, 210 mg of famciclovir is converted to diacetyl penciclovir in a yield of 82 %. The optimized protocol enables the preparative synthesis of oxidized aldehyde oxidase metabolites of drugs.